Circular RNA Expression: Its Potential Regulation and Function in Abdominal Aortic Aneurysms. (30th June 2021) - Han, Yanshuo; Zhang, Hao; Bian, Ce; Chen, Chen; Tu, Simei; Guo, Jiahui; Wu, Yihao; Böckler, Dittmar; Zhang, Jian
Abstract : Abdominal aortic aneurysms (AAAs) have posed a great threat to human life, and the necessity of its monitoring and treatment is decided by symptomatology and/or the aneurysm size. Accumulating evidence suggests that circular RNAs (circRNAs) contribute a part to the pathogenesis of AAAs. circRNAs are novel single-stranded RNAs with a closed loop structure and high stability, having become the candidate biomarkers for numerous kinds of human disorders. Besides, circRNAs act as molecular "sponge" in organisms, capable of regulating the transcription level. Here, we characterize that the molecular mechanisms underlying the role of circRNAs in AAA development were further elucidated. In the present work, studies on the biosynthesis, bibliometrics, and mechanisms of action of circRNAs were aims comprehensively reviewed, the role of circRNAs in the AAA pathogenic mechanism was illustrated, and their potential in diagnosing AAAs was examined. Moreover, the current evidence about the effects of circRNAs on AAA development through modulating endothelial cells (ECs), macrophages, and vascular smooth muscle cells (VSMCs) was summarized. Through thorough investigation, the molecular mechanisms underlying the role of circRNAs in AAA development were further elucidated. The results demonstrated that circRNAs had the application potential in the diagnosis and prevention of AAAs in clinical practice. The study of circRNA regulatory pathways would be of great assistance to the etiologic research of AAAs.